Phylogeny of Hepatocystis parasites of Australian flying foxes reveals distinct parasite clade. Issue 2 (August 2018) - Schaer, Juliane; McMichael, Lee; Gordon, Anita N.; Russell, Daniel; Matuschewski, Kai; Perkins, Susan L.; Field, Hume; Power, Michelle
Abstract: Hepatocystis parasites are close relatives of mammalian Plasmodium species and infect a range of primates and bats. Here, we present the phylogenetic relationships of Hepatocystis parasites of three Australian flying fox species. Multilocus phylogenetic analysis revealed that Hepatocystis parasites of Pteropus species from Australia and Asia form a distinct clade that is sister to all other Hepatocystis parasites of primates and bats from Africa and Asia. No patterns of host specificity were recovered within the Pteropus -specific parasite clade and the Hepatocystis sequences from all three Australian host species sampled fell into two divergent clades. Graphical abstract: Image 1 Highlights: First molecular phylogeny of Hepatocystis parasites in Australian flying foxes. Hepatocystis parasites of Pteropus form a distinct clade. Lack of host species specificity as distinct hallmark of Hepatocystis parasites.